Pengembangan Aplikasi Layanan Elektronik Pengaduan Masyarakat (E-Adumas) untuk Warga Desa dengan Gammu SMS Gateway - Ferdiansyah, Doddy; Sudrajat, Jajat (Jurnal Computech & Bisnis (e-journal), 2021)
Public services for rural communities require special attention, in the context of increasing public rights from the community. Service performance is often perceived as not good or even to the point of disrupting activities and reducing public satisfaction. Submission of citizen complaints, especially related to public services in the village, is currently identified as very low because there are no supporting facilities that make it easier for residents to submit complaints without having to come to the Village Hall. The purpose of this research is to build a means of submitting complaints by utilizing GSM network access and cellular telephones, so that village staff can directly see it in the form of an Information Board System. The research was conducted by conducting a feasibility study, analysis of application requirements and problems, design, application development, and implementation. The application is built with a special framework in the form of an SMS Gateway and modified according to the conditions and characteristics in the village environment. The final result of the research is a public complaint service application and Information Board System technology, which can be used by all villagers to submit their complaints, and vice versa by village staff for complaint management and to send public information to village communities. The final product can later be developed for use at the village level, to monitor complaints from all villagers, and can be developed to the sub-district level to monitor community complaints at the sub-district level.